Potential determinants of early discontinuation of Etonogestrel implant: a cohort prospective study - Zeena Helmi (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the frequency of early discontinuation of Implanon as a method of contraception. Method: The cohort prospective study was at the Obstetrics and Gynaecology Department, Al-Yarmouk Teaching Hospital, Baghdad, Iraq from January 2017 to January 2021, after approval from the ethics review committee of the College of Medicine, Al-Mustansiriyha University, Bghadad, Iraq, and comprised women of child-bearing age seeking long-acting contraception. The participants received Implanon, an etonorgestril implant, under local anaesthesia, and were followed up for 12 months for possible side effects. Data was analysed using SPSS 26. Results: There were 115 women with mean age 29.8±6 years (range: 15-44 years) and mean body mass index 27±4.9 kg/m2. Early discontinuation of the plant was done by 32(27.8%) subjects, and the overall incidence of early Implanon removal per 1,000 women per month was 14.47 (95% confidence interval: 10.24-20.47). Lower body mass index, dizziness and insertion-site side effects were the potential determinants of early discontinuation (p<0.05). Conclusions: More than a quarter of the sample opted for early Implanon discontinuation. Low body mass index, dizziness and insertion-site side effects were potential determinants of early removal. Key Words: Etonogestrel, Anaesthesia, Dizziness, Gynaecology, Incidence, Contraception